In vivo blue light illumination for optogenetic inhibition: effect on local temperature and excitability of the rat hippocampus. (24th December 2021) - Acharya, Anirudh R; Vandekerckhove, Bram; Larsen, Lars Emil; Delbeke, Jean; Wadman, Wytse J; Vonck, Kristl; Carette, Evelien; Meurs, Alfred; Vanfleteren, Jan; Boon, Paul; Missinne, Jeroen; Raedt, Robrecht
Abstract: Objective. The blue light-activated inhibitory opsin, stGtACR2, is gaining prominence as a neuromodulatory tool due its ability to shunt-inhibit neurons and is being frequently used in in vivo experimentation. However, experiments involving stGtACR2 use longer durations of blue light pulses, which inadvertently heat up the local brain tissue and confound experimental results. Therefore, the heating effects of illumination parameters used for in vivo optogenetic inhibition must be evaluated. Approach. To assess blue light (473 nm)-induced heating of the brain, we used a computational model as well as direct temperature measurements using a fiber Bragg grating (FBG). The effects of different light power densities (LPDs) and pulse durations on evoked potentials (EP) recorded from dentate gyrus were assessed. For opsin-negative rats, LPDs between 127 and 636 mW mm −2 and pulse durations between 20 and 5120 ms were tested while for stGtACR2 expressing rats, LPD of 127 mW mm −2 and pulse durations between 20 and 640 ms were tested. Main results. Increasing LPDs and pulse durations logarithmically increased the peak temperature and significantly decreased the population spike (PS) amplitude and latencies of EPs. For a pulse duration of 5120 ms, the tissue temperature increased by 0.6 °C–3.4 °C. All tested LPDs decreased the PS amplitude in opsin-negative rats, but 127 mW mm −2 had comparatively minimal effects and a significant effect of increasing light pulse duration was seen from 320 ms and beyond. This corresponded with an average temperature increase of 0.2 °C–1.1 °C at the recorded site. Compared to opsin-negative rats, illumination in stGtACR2-expressing rats resulted in much greater inhibition of EPs. Significance. Our study demonstrates that light-induced heating of the brain can be accurately measured in vivo using FBG sensors. Such light-induced heating alone can affect neuronal excitability. Useful neuromodulation by the activation of stGtACR2 is still possible while minimizing thermal effects.